2017
DOI: 10.3847/1538-4357/aa7af2
|View full text |Cite
|
Sign up to set email alerts
|

Multi-frequency Scatter Broadening Evolution of Pulsars. I

Abstract: We present multi-wavelength scatter broadening observations of 47 pulsars, made with the Giant Metre-wave Radio Telescope (GMRT), Ooty Radio Telescope (ORT) and Long Wavelength Array (LWA). The GMRT observations have been made in the phased array mode at 148, 234, and 610 MHz and the ORT observations at 327 MHz. The LWA data sets have been obtained from the LWA pulsar data archive. The broadening of each pulsar as a function of observing frequency provides the frequency scaling index, α. The estimations of α h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 28 publications
3
24
1
Order By: Relevance
“…This suggests the RM(φ) curve is potentially time variable. Krishnakumar et al (2017) observed scatter broadening at lower frequencies for this pulsar and estimated a timescale of 0.06 ms at 1 GHz, which is relatively low. The largest ∆(V/I)(φ) variations occur at longitude ∼ 173 • , which is not where V changes most rapidly, suggesting a magnetospheric origin for the RM(φ) variations.…”
Section: Pulsars With Significant Rm Variationsmentioning
confidence: 61%
See 2 more Smart Citations
“…This suggests the RM(φ) curve is potentially time variable. Krishnakumar et al (2017) observed scatter broadening at lower frequencies for this pulsar and estimated a timescale of 0.06 ms at 1 GHz, which is relatively low. The largest ∆(V/I)(φ) variations occur at longitude ∼ 173 • , which is not where V changes most rapidly, suggesting a magnetospheric origin for the RM(φ) variations.…”
Section: Pulsars With Significant Rm Variationsmentioning
confidence: 61%
“…There are two wiggles in the PA swing towards the trailing edge of the profile, and this region is where significant RM(φ) variations (∼ 5 rad m −2 ) occur. Krishnakumar et al (2017) estimated a scattering timescale of 0.13 ms at 1GHz, which is low. If the observed RM variations were caused by scattering, ∆(V/I)(φ) variations would be expected at most longitudes, as Stokes V is steeply changing across the entire profile.…”
Section: Pulsars With Significant Rm Variationsmentioning
confidence: 92%
See 1 more Smart Citation
“…P (pulse period) was taken from the ATNF pulsar catalog 3 , whereas W (width of the pulse) was corrected for pulse scatter-broadening from W 50 4 as explained below. The effect of scatter broadening was taken into account by convolving a top hat pulse of width W 50 with the exponential scatter-broadening function using characteristic time-scales obtained from Krishnakumar et al (2017a) and NE2001 model (Cordes & Lazio 2002). The final width W is taken as 50% of the peak height of the convolved pulse profile.…”
Section: Sample Selection and Integration Timementioning
confidence: 99%
“…The closest compact source to HB9 is the pulsar PSR B0458+46/PSR J0502+4654 that is located within the radio continuum shell of the SNR (Krishnakumar et al 2017). This pulsar is at a distance of 1.79 kpc and so far no gammaray emission has been detected from it.…”
Section: Introductionmentioning
confidence: 99%